Gender Awareness in Islamic Education: The Pioneering Case of Indonesia in a Comparison with Pakistan - Kull, Ann (Studia Islamika, 2012)
This article analyzes the development of gender awareness in Islamic education in Indonesia and Pakistan in general, and the inclusion of a gender perspective in particular. The current situation in Islamic education is a result of larger national contexts, not least concerning the factors focused upon in this study — educational reform, intellectual milieu, female student enrollment, political development and women’s rights movements. Traditionalist ulama and scholars educated in the Middle East have in both countries similarly questioned the Islamic knowledge and legitimacy of reformist scholars — women and men alike — and these opponents have been more influential in Pakistan than in Indonesia. The Indonesian gender regime in Islamic education is no longer fully male– dominated, and the patriarchal content in Islamic educational material is occasionally questioned and exchanged. However, in Pakistan the impact of women on the prevailing male–dominated gender regime and patriarchal content in Islamic education is at best seminal.DOI: 10.15408/sdi.v19i3.354